1998
DOI: 10.1038/sj.onc.1202098
|View full text |Cite
|
Sign up to set email alerts
|

The t(2;3)(q21;q27) translocation in non-Hodgkin's lymphoma displays BCL6 mutations in the 5′ regulatory region and chromosomal breakpoints distant from the gene

Abstract: The BCL6 gene, mapped at the chromosomal band 3q27, encodes a POZ/Zinc ®nger transcription repressor protein. It is frequently activated in Non-Hodgkin's lymphomas (NHL) by translocations with breakpoints clustering in the 5' major breakpoint region (MBR) as well as by mutations in the same region. The translocations lead to BCL6 activation by substitution of promoters of rearranging genes derived from the reciprocal chromosomal partners such as IG. We report the molecular genetic analysis of a novel t(2;3)(q2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…We found that the nucleotide sequences of the ES and IS regions in the BCL6 gene (Bernardin et al, 1997) are highly conserved between humans and mice (100% homology in ES and 65.9% in IS). In addition, the deletions within the BCL6 gene in the ®ve cases of lymphomas previously reported were also found to occur in the ®rst exon-intron boundary region spanning ES and IS (Bernardin et al, 1997;Chen et al, 1998;Nakamura et al, 1996;1999). These observations strongly suggest that the ES and IS regions have important roles in the transcriptional regulation of the BCL6 gene, and their alteration may be a crucial event in lymphomagenesis.…”
mentioning
confidence: 56%
“…We found that the nucleotide sequences of the ES and IS regions in the BCL6 gene (Bernardin et al, 1997) are highly conserved between humans and mice (100% homology in ES and 65.9% in IS). In addition, the deletions within the BCL6 gene in the ®ve cases of lymphomas previously reported were also found to occur in the ®rst exon-intron boundary region spanning ES and IS (Bernardin et al, 1997;Chen et al, 1998;Nakamura et al, 1996;1999). These observations strongly suggest that the ES and IS regions have important roles in the transcriptional regulation of the BCL6 gene, and their alteration may be a crucial event in lymphomagenesis.…”
mentioning
confidence: 56%
“…13,43,44 This study aimed at defining the incidence of BCL6 gene alterations in the different subgroups of DLBCL as defined by GEP. In addition, we have (10) 4 (40%) 6 (60%) UNCL (27) 10 (37%) 17 (63%) Total (138) 78 (56%) 60 (44%)…”
Section: Discussionmentioning
confidence: 99%
“…8 Briefly, a BCL6 break-apart probe (BAP; Abbott-Vysis, Downers Grove, IL, USA) was used to detect BCL6 translocations at major breakpoint region (MBR) and a BCL6 home-brew BAP (Clone RP11-1144D2 and RP11-67E18) at the alternative breakpoint region (ABR) (78/133 cases). 27,28 Nuclei were counterstained with 4,6-diamidino-2-phenylindole (DAPI) in Antifade solution and the slides were visualized using an Olympus BX51 fluorescence microscope. Images were captured and archived using Cyto Vision software (Applied Imaging, Santa Clara, CA, USA).…”
Section: Immunohistochemical Staining Of Tissue Sectionsmentioning
confidence: 99%
“…Chromosomal translocations involving the 3q27 region have been already recognized as B-NHL-related abnormalities occurring in approximately 40% of DLBCL and in 5% to 10% of follicular lymphomas. 61,62 The t(3q27) results in a deregulation of the BCL6 proto-oncogene, encoding a zinc finger transcription repressor either by the Ig gene clusters at 2p12, 14q32, and 22q11, or by a variety of other genomic loci. [63][64][65] It has been shown that the BCL6 protein is expressed predominantly in normal GC B cells and related lymphomas, and is required for GC formation and function.…”
Section: Discussionmentioning
confidence: 99%